Expansion of the Deposit Base of Commercial Banks and Population Literacy Interrelationship Issues (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article discusses the innovative economy and digitalization in banks. increasing the types of services and their share, the deposit base of commercial banks to expand, attract banks' resources and use them for effective purposes. The level of financial literacy of the population is integral to managing the placement outlines current research issues and their priority areas done.